EFFECT OF SENILE ASTHENIA ON THE SEVERITY OF THE POSTOPERATIVE PERIOD IN ELDERLY AND SENILE PATIENTS WITH GASTRIC AND DUODENAL ULCER PERFORATION - Danyliuk, M.B.; Zavhorodniy, S.M.; Kubrak, M.A.; Kapshytar, O.V.; Bambyzov, L.M.; Yareshko, N.O.; Bachurin, A.V. (World of Medicine and Biology, 2023)
The study evaluates the effect of senile asthenia on the severity of the postoperative period in elderly and senile patients with perforation of gastric and duodenal ulcers. The total number of patients was 80 (100.0 %) aged 60 to 89 years. The condition was assessed using the P-POSSUM scale, and senile asthenia syndrome was assessed using the Edmonton Frail scale. Based on the diagnosis of asthenia, the distribution was made: group A – 30 (37.5 %) patients without asthenia and group B – 50 (62.5 %) patients with asthenia. The groups were comparable in terms of diagnosis and performed surgery. When comparing, it was determined that senile asthenia significantly affects the severity of the condition according to P-POSSUM in the group without asthenia (group A) – 32±6.8, in the group with asthenia (group B) – 49±6.7, p
Keywords: senile asthenia; ulcer; peritonitis; old age